Transcriptomic characterization of maturing neurons from human neural stem cells across developmental time points - Kimia Hosseini; Gaëtan Philippot; Sara B. Salomonsson; Andrea Cediel-Ulloa; Elnaz Gholizadeh; Robert Fredriksson (IBRO Neuroscience Reports)
Neurodevelopmental studies employing animal models encounter challenges due to interspecies differences and ethical concerns. Maturing neurons of human origin, undergoing several developmental stages, present a powerful alternative. In this study, human embryonic stem cell (H9 cell line) was differentiated into neural stem cells and subsequently matured into neurons over 30 days. Ion AmpliSeq™ was used for transcriptomic characterization of human stem cell-derived neurons at multiple time points. Data analysis revealed a progressive increase of markers associated with neuronal development and astrocyte markers, indicating the establishment of a co-culture accommodating both glial and neurons. Transcriptomic and pathway enrichment analysis also revealed a more pronounced GABAergic phenotype in the neurons, signifying their specialization toward this cell type. The findings confirm the robustness of these cells across different passages and demonstrate detailed progression through stages of development. The model is intended for neurodevelopmental applications and can be adapted to investigate how genetic modifications or exposure to chemicals, pharmaceuticals, and other environmental factors influence neurons and glial maturation.